Hybrid Interactive Media Based on Project-Based Learning (PjBL) with VR 360 Technology: An Innovation in Economics Learning for University Students - Ulfa, Noviana Mariatul; Kurniawan, Nurhafit (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop Hybrid Interactive Media based on Project-Based Learning (PjBL) integrated with 360-degree Virtual Reality (VR) technology to enhance students’ conceptual understanding and 21st-century skills. This research employed a Research and Development (R&D) approach using the ADDIE model, encompassing needs analysis, prototype design, media development, implementation, and evaluation. Data were collected through expert validation sheets, lecturer and student response questionnaires, and learning outcome tests, and were analyzed using descriptive statistics and paired-sample t-tests. Expert assessments indicated that the media was highly valid (M = 4.42), while practicality was supported by lecturers’ responses (M = 4.36, highly practical) and students’ responses (M = 4.29, practical). Effectiveness testing using a one-group pre-test–post-test design showed significant improvement in learning outcomes, with mean scores increasing from 63.1 to 82.5 (t(29) = 10.12, p < 0.001). Students’ critical thinking skills also improved from 2.8 to 4.0 (scale 1–5). These findings indicate that integrating VR 360 with PjBL effectively enhances conceptual understanding, critical thinking, and learning motivation in economics education. This study contributes to the literature by extending the application of VR technology beyond STEM fields into economics education and offers practical insights for innovative learning in higher education.